STRATEGI PEMBELAJARAN PAUD BERBASIS KEARIFAN LOKAL PADA ERA NEW NORMAL DI TK OMAH DOLANAN YWKA YOGYAKARTA - Alfiyanti Nurkhasyanah; Aninditya Sri (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
The importance of the strategies that teachers implement in PAUD learning, both as a form of development in the development of the child's aspects. PAUD learning strategies based on local wisdom integrate various cultural values to be introduced into the world of children, at an early age. The problem in this study is based on the phenoma that occurred in TK Omah Dolanan YWKA Yogyakarta which realizes local wisdom-based learning strategies. The purpose of this study was to see how the form of learning strategies was carried out by TK Omah Dolanan YWKA Yogyakarta. The research method used by researchers is descriptive qualitative. The data technique uses documentation, interviews and observations. The results of this study indicate that the form of local wisdom-based learning strategies used is in the form of videos that the teacher makes in the form of enrichment of Javanese language that is in the child. Then the final results can be collected by assignments in the form of videos sent via the Whatsapp Group.